1970
DOI: 10.1002/aic.690160222
|View full text |Cite
|
Sign up to set email alerts
|

Radial migration of spherical particles in couette systems

Abstract: Several studies have been made in Couette systems of the primary motion (angular translation and rotation) of spheres suspended in viscous liquids. Radial migration trajectories, however, have been unreported for single spheres.In this study, a prediction of radial migration is developed and compared with experimental measurements. The predicted trajectories were found to agree well with the measured ones.Ultimately, radiolly migrating spheres reached an equilibrium position located approximatelY midway betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 5 publications
7
31
0
Order By: Relevance
“…Cell concentrations very close to the mesh are decreased approximately to the half of the bulk concentration. Such a depletion of cells in the vicinity of the sieve is consistent with the lateral migration observed in Taylor-Couette flow (Halow and Wills 1970). Therefore, it can be stated that the CFD model predicts the occurrence of lateral particle migration.…”
Section: Resultssupporting
confidence: 83%
“…Cell concentrations very close to the mesh are decreased approximately to the half of the bulk concentration. Such a depletion of cells in the vicinity of the sieve is consistent with the lateral migration observed in Taylor-Couette flow (Halow and Wills 1970). Therefore, it can be stated that the CFD model predicts the occurrence of lateral particle migration.…”
Section: Resultssupporting
confidence: 83%
“…When the viscosity of a suspension is measured in a Couette viscometer, the dispersed spheres tend to migrate away from the walls (Halow and Wills, 1970), creating an inhomogeneous suspension. Similar concentration inhomogeneities occur in other types of viscometers (see Leal, 1980).…”
Section: Comparison With Experimental Datamentioning
confidence: 99%
“…The closed-form solutions for the lateral force of neutrally buoyant spheres were in good agreement with experimental observations in terms of equilibrium positions and trajectories of migrations. [39][40][41] The general form 6 of the lift force indicated that the interaction of the disturbance stresslet and its wall correction with the bulk shear produces a force toward the centerline, while the interaction between the stresslet and the curvature of the bulk velocity profile tends to cause migration in the direction of increasing (absolute) shear rate, where the stresslet is the symmetric first moment of the surface stress of a body in a flowing fluid.…”
Section: Theoretical Analysis a Lift Forcementioning
confidence: 99%